Plaider la « bonne gouvernance sécuritaire » au Maroc : Domestiquer les savoirs de réforme en régime de contrainte consensuelle - Irene Lizzola (L’Année du Maghreb)
Since the conclusion of the Equity and Reconciliation Commission’s work in 2006, the establishment of “good security governance” has become the leitmotif of attempts to reform security institutions. During this pivotal moment, the Moroccan regime opened up the outsourcing of the production of reform knowledge relating to security, through the progressive association of NGOs and transnational actors in the development of public policies. If, on the one hand, this reformist lexicon promotes NGOs’ depoliticized commitment and the institutional construction of a liberal appearance, on the other, it constitutes a tool in the hands of professionalized and internationalized NGOs, which allows them to keep the discussion open with the authorities around the security issue. The regime, in search of relegitimization, endorses the rhetoric of co-production of public policies, to be guaranteed by the involvement of the “civil society”.The confrontation between the actors is based on a consensus which results in common alignment on the legalistic and managerial treatment of security reform. However, this consensus appears to be constrained, at the level of the threshold of criticism tolerated by security institutions. Thus, the confrontation between the parties is part of a regime of consensual constraint. In this register, the consensus is built around the reciprocal obligation to validate a legalist and managerial reformist discourse, strongly internationalized and deconflictualizing the issues, which unites the parties, as well as the mutual acceptance of the logics which accompany partnership selectivity governing the participation of associative and transnational actors in the “co-production” of public action. Here, the different actors play with these constraint factors, from the moment when each party benefits from the participation in the partnership dynamic. Although framed, this allows associative, transnational and institutional actors to legitimize each other as bearers of good reformist recipes.Firstly, we will question the construction of the reformist discourse relating to the management of security, by questioning the anchoring of the latter in the vocabulary of transitology. Here, we will focus on the domestication of the concept of “security governance”, as it was developed by the Center for Human Rights and Democracy Studies (CEDHD), as an intermediary and “broker” responsible for the establishment of dialogue between DCAF (Geneva Center for Security Sector Governance) and Moroccan security institutions.Secondly, we will highlight the other side of the coin of the rhetoric of the “co-construction” of security, advocated by the security forces. In fact, this discourse is accompanied by the establishment of constrained participation frameworks, the partnership selectivity at work only allowing a partial association of “civil society” wishing to participate in public security policies.Finally, we will consider the practices of raising awareness of the reform of security governance, emphasizing the legalistic, managerial and managerial nature of the discourses which justify them, and which frame their concrete achievements. Here, the developmentalist discourse, strongly neoliberalized, imposes itself as the shared grammar allowing the most professionalized, internationalized, and least protesting actors to invest in the field of public security policies.This article is based on fieldwork carried out in Morocco between 2019 and 2022, for a discontinuous period of nine months, in the cities of Rabat and Casablanca, conducted both at the headquarters of the associations studied (CEDHD, FVJ, Institut Prometheus), through semi-structured interviews with their founding members (four of whom are used in this article) and consultation of their archives and publications (reports, studies, surveys), and, through non-participant observations, at activities (press conferences, seminars) organized by them, in partnership with institutions and the DCAF. The on-site fieldwork was supplemented by occasional surveys carried out remotely, particularly during the Covid-19 health crisis (from March 2020 to August 2021), which enabled semi-structured interviews to be conducted, written sources to be collected (grey literature produced by the NGOs and their partners) and activities to be monitored (conferences, seminars), broadcast on the associations’ social networks. These various empirical materials are the subject of a qualitative analysis that combines the study of actors’ discourse, their trajectories and their engagement practices (partnership, associative investigation, training, etc.). The analysis questions the construction of “consensual” dialogue, as well as the constraints that structure it, between the actors involved in the circulation of reform knowledge relating to security governance.